Grand challenges in biomolecular condensates: structure, function, and formation - Hatters, Danny M. (Frontiers in Biophysics, 2023)
Biomolecular condensates describe concentrated nonstoichiometric assemblies of biomolecules that can form by a range of different mechanisms (1). Biomolecular condensates can arise by phase separation, which in biology involves the demixing of a water-soluble polymer into two co-existing phases: a polymer-dilute phase and a polymer-dense phase. Coacervates describe phase separation mediated by a third element, which may typically be a ligand (such as RNA) to the polymer (such as a protein) that undergoes phase separation. Protein aggregation into amyloids and amorphous aggregates, and the formation of RNA granules, represent other forms of biomolecular condensates. The assembly of proteins and other biomolecules into complexes is a fundamental feature for the execution of biological functions. Biomolecular condensates are a natural variation of the assembly theme. There is an incredible complexity and diversity to how condensates form, are regulated and are structured (reviewed recently in (2)). And there is incredible diversity to how condensates are used by nature to drive biological functions and how when their assemblies go wrong, they can drive disease mechanisms, such as amyloids in neurodegeneration.